The Effect of Shock Wave and Bubble Coalescence in Spherical Cloud of Cavitation Bubbles on Maximum Temperature Inside Central Bubbles (Journal of Atomic and Molecular Sciences, 2014)
We present a theoretical analysis of the influence of shock wave propagatingin bubble cluster and bubble combining in expansion phase on maximum temperatureinside central bubbles. By using adiabatic model and assumptions for simplifying theproblem we find that these parameters have significant effects on temperature rising incompression phase. In particular, the shock wave, in comparison to bubble combining,has a greater impact on the maximum temperature.
Keywords: shock wave; adiabatic model; compression phase; bubble combining.